Comparison of hospital length of stay between hospitalized non-valvular atrial fibrillation patients treated with either apixaban or warfarin. Issue 3 (October 2015) - Farr, Amanda M.; Jing, Yonghua; Johnston, Stephen; Trocio, Jeffrey; Singhal, Shalabh; Bruno, Amanda; Graham, John
Abstract: Background. Hospital length of stay (LOS) is an important cost driver for hospitals and payers alike. Hospitalized non-valvular atrial fibrillation (NVAF) patients treated with apixaban may have shorter LOS than those treated with warfarin because of the absence of need for INR monitoring in apixaban. Thus, this study compared hospital LOS between hospitalized NVAF patients treated with either apixaban or warfarin. Methods. This was a retrospective, observational cohort study based on a large US database including diagnosis, procedure, and drug administration information from >600 acute-care hospitals. Patients selected for study were aged ≥18 years and had a hospitalization record with an ICD-9-CM diagnosis code for atrial fibrillation (AF) in any position from 1 January 2013 to 28 February 2014 (index hospitalization). Patients with diagnoses indicative of rheumatic mitral valvular heart disease or a valve replacement procedure during index hospitalization were excluded. Patients were required to have been treated with either apixaban or warfarin, and not treated with rivaroxaban or dabigatran, during index hospitalization. Apixaban patients were propensity score (PS) matched to warfarin patients at a 1:1 ratio, using patient demographic/clinical and hospital characteristics. The study outcome was hospital LOS, calculated as discharge date minus admission date; a sensitivity analysis calculated hospital LOS as discharge date minus first anticoagulant administration date. Sub-analyses were conducted among patients with a primary diagnosis of AF. Results. The study included 832 apixaban patients matched to 832 warfarin patients. Mean [standard deviation (SD)] and median hospital LOS were significantly ( p < 0.001) shorter in apixaban patients (4.5 [4.2] and 3 days) than in warfarin patients (5.4 [5.0] and 4). Results were consistent in the sensitivity and sub-analyses. Conclusions. Among NVAF patients, apixaban treatment was associated with shorter hospital LOS when compared with warfarin treatment. These findings may have important clinical and economic implications for hospitals, payers, and patients.